2000
DOI: 10.1177/104063870001200310
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Long-Term Shedding Pattern ofSalmonellaSerovarCholeraesuisFollowing Experimental Infection of Neonatal Piglets

Abstract: In the United States, swine salmonellosis is most often attributed to infections by Salmonella serovar choleraesuis. As a host-adapted pathogen rarely found in nonswine sources, S. choleraesuis is thought to be spread primarily via horizontal transmission, with carrier animals playing an important role. Little has been reported regarding infection of neonatal piglets, particularly regarding their potential to become carriers. Evidence reported herein demonstrates that piglets experimentally infected by S. chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…1 In the present study, none of the isolates were S. choleraesuis. Although toxic to S. choleraesuis, tetrathionate has been suggested as the medium of choice for enrichment of other Salmonella species (other than S. choleraesuis) in fecal specimens of carrier animals.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…1 In the present study, none of the isolates were S. choleraesuis. Although toxic to S. choleraesuis, tetrathionate has been suggested as the medium of choice for enrichment of other Salmonella species (other than S. choleraesuis) in fecal specimens of carrier animals.…”
mentioning
confidence: 78%
“…Numerous preenrichments, particularly peptone water, have been used for culture of salmonellae. 1 When culturing samples from swine and their environment for Salmonella enterica serovar Choleraesuis, GN Hajna broth has been reported to be superior to other selective enrichments. 1,2,6-8 However, when culturing for salmonellae other than Salmonella Choleraesuis, tetrathionate broth has been routinely utilized for enrichment.…”
mentioning
confidence: 99%
“…Studies of swine fecal samples subjected to multiple methods of selective enrichment for isolation of Salmonella have demonstrated that no culture method is 100% sensitive and that the serotypes isolated from the same sample differed by the culture method used, suggesting that serotypes differ in their susceptibilities to selective agents in enrichment media (24,49,54). The Salmonella serotype Choleraesuis, which is associated with swine, has been demonstrated to be sensitive to selective enrichment methods (2,54). Salmonella Choleraesuis was not isolated from any of the 4,560 carcasses sampled during this study, suggesting that the selective enrichment used in this study may not be suitable for the isolation of this serotype.…”
Section: Discussionmentioning
confidence: 99%
“…The number of confirmed Salmonella was determined for each sample by multiplying the number of presumptive Salmonella colonies by the percentage of overnight cultures confirmed to contain Salmonella by invA PCR (9). The number of confirmed Salmonella was then reported as log CFU per 100 cm 2 . The lower limit of detection for prescald carcass samples was 1.4 log CFU/100 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Choleraesuis has directly been isolated from the lung, liver, spleen, and other organs of diseased pigs [15,16]. In several recent studies of experimental infection of pigs with S. Choleraesuis, Rappaport Vassiliadis broth (RV) [19] was used as the enrichment broth [1,10,16]. Besides, Hajnatetrathionate broth (HTT) has widely been used as an enrichment broth for Salmonella in Japan [2,4,13,14].…”
mentioning
confidence: 99%